The Semantics of White in Russian, Polish and Lithuanian: A Contrastive Analysis - Ušinskienė, Viktorija (Vilnius University Open Series, 2021)
The paper presents the results of the contrastive semantic analysis of the Russian lexeme белый ‘white’ and its Polish and Lithuanian equivalents — biały / baltas. The research aimed at comparing the collocability of the terms of ‘white’ with names of various objects and phenomena (both in the literal and figurative senses) including the identification of the prototype references and connotative meanings. The analysis has illustrated that Rus. белый / Pol. Biały / Lith. baltas have similar ranges of use and develop almost identical connotations. In all languages, whiteness is interpreted as the lightest color whose qualitative prototype pattern is SNOW, and the quantitative prototype pattern is DAYLIGHT. The prototype references create characteristic connotation chains: ‘as white as snow’ — ‘pure (also morally)’ — ‘innocent’ — ‘honest’ — ‘good’; ‘as white (light) as daylight’ — ‘transparent’ — ‘obvious’ — ‘legal’ — ‘good’. The differences between the discussed units are mainly noted on the level of the lexical components with individual connotations. Apart from the few phenomena that are culturally specific, in the use of the lexemes белый / biały / baltas there are no major discrepancies. Instead, it is possible to note only the asymmetry as it is in the case with the related meanings ‘clarity’ and ‘legality’.
Keywords: color terms; semantics of color; white color; contrastive analysis